Review: The evolution of peptidergic signaling in Cnidaria and Placozoa, including a comparison with Bilateria - Hauser, Frank; Koch, Thomas L.; Grimmelikhuijzen, Cornelis J. P. (Frontiers in Endocrinology, 2022)
Bilateria have bilateral symmetry and are subdivided into Deuterostomia (animals like vertebrates) and Protostomia (animals like insects and mollusks). Neuropeptides occur in both Proto- and Deuterostomia and they are frequently structurally related across these two lineages. For example, peptides belonging to the oxytocin/vasopressin family exist in both clades. The same is true for the G protein-coupled receptors (GPCRs) of these peptides. These observations suggest that these neuropeptides and their GPCRs were already present in the common ancestor of Proto- and Deuterostomia, which lived about 700 million years ago (MYA). Furthermore, neuropeptides and their GPCRs occur in two early-branching phyla that diverged before the emergence of Bilateria: Cnidaria (animals like corals and sea anemones), and Placozoa (small disk-like animals, feeding on algae). The sequences of these neuropeptides and their GPCRs, however, are not closely related to those from Bilateria. In addition, cnidarian neuropeptides and their receptors are not closely related to those from Placozoa. We propose that the divergence times between Cnidaria, Placozoa, and Bilateria might be too long for recognizing sequence identities. Leucine-rich repeats-containing GPCRs (LGRs) are a special class of GPCRs that are characterized by a long N-terminus containing 10-20 leucine-rich domains, which are used for ligand binding. Among the ligands for LGRs are dimeric glycoprotein hormones, and insulin-like peptides, such as relaxin. LGRs have been found not only in Proto- and Deuterostomia, but also in early emerging phyla, such as Cnidaria and Placozoa. Humans have eight LGRs. In our current review, we have revisited the annotations of LGRs from the sea anemone Nematostella vectensis and the placozoan Trichoplax adhaerens. We identified 13 sea anemone LGRs and no less than 46 LGRs from T. adhaerens. All eight human LGRs appear to have orthologues in sea anemones and placozoans. LGRs and their ligands, therefore, have a long evolutionary history, going back to the common ancestor of Cnidaria and Placozoa.